Deepfake dan Krisis Kejujuran di Era Artificial Intelligence: Analisis Dilema Moral dalam Perspektif Al-Ghazali - Siti Rahayu; Elvira Purnamasari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Advances in Artificial Intelligence (AI) technology, particularly Generative Adversarial Networks (GANs), have given rise to the phenomenon of deepfakes technology capable of authentically manipulating audio-visual reality while producing content that is, in fact, fake. The August 2025 deepfake video involving Finance Minister Sri Mulyani serves as clear evidence of a digital integrity crisis that is eroding public trust in Indonesia. Although technical and regulatory solutions continue to be developed, the moral dimension of this crisis has not been thoroughly examined through the framework of classical Islamic ethics, particularly the thought of Al-Ghazali. This study aims to analyze the moral dilemmas posed by deepfake technology and to examine its relevance to the crisis of truthfulness in the digital age from the perspective of Abu Hamid al-Ghazali’s thought. Using a qualitative method through library research with the primary source being the book Ihya’ Ulum al-Din, this study applies a descriptive-analytical approach to examine the phenomenon of digital manipulation and uncover its ethical dimensions from Al-Ghazali’s perspective. The results indicate that deepfakes constitute a modern form of kadzib that creates a false reality and triggers a crisis of public trust. From Al-Ghazali’s perspective, this phenomenon contradicts the principle of sidq as well as the objectives of maqasid al-shariah. Therefore, the values of sidq, amanah, tabayun, and tazkiyatun nafs serve as an ethical framework in the production, distribution, and consumption of digital information to strengthen technical approaches to maintaining integrity and public trust.